Respuesta :

The explicit formula for calculating the sum is

[tex]S_N=\frac{n(n-1)}{2} \cdot\frac{n(n+1)}{2}[/tex]

The sum of the nth term of a sequence is expressed as;

[tex]S_n=\frac{n}{2}(2a+(n-1)d)[/tex]

a is the first term

d is the common difference

n is the number of terms

For the sequence  0 + 1 + 2 + 3  +...

[tex]S_n=\frac{n}{2}(2(0)+(n-1)1)\\S_n= \frac{n}{2}(n-1)\\S_n= \frac{n(n-1)}{2}[/tex]

Similarly for the sequence:

1 + 2+ 3 + 4+...

[tex]S_n=\frac{n}{2}(2(1)+(n-1)1)\\S_n= \frac{n}{2}(2+n-1)\\S_n= \frac{n(n+1)}{2}[/tex]

Taking the product of the sum to get the explicit formula for calculating the sum

[tex]S_N=\frac{n(n-1)}{2} \cdot\frac{n(n+1)}{2}[/tex]

Learn more here: https://brainly.com/question/24547297